Analysis of the Influence of Infinite Mindset Through Innovation and Learning Ability on Business Sustainability - Aulia, Muhammad Reza; Salsabila, Cut; Nasution, Anisah; Fuqara, Fanthasir Awwal; Azrani, Utary; Pratiwi, Henny; Tannady, Hendy (Malikussaleh University, Aceh, Indonesia, 2025)
In today's era of globalisation, business development is growing rapidly and undergoing continuous metamorphosis. The coffee business itself has a long history of driving economic growth in Indonesia. Geographically, Indonesia's soil is ideal for the microclimate that supports coffee growth and production. According to the 2023 Indonesian Statistics report from the Central Statistics Agency (BPS), Indonesian coffee production reached 794.8 thousand tons in 2022, an increase of approximately 1.1% compared to the previous year. Methods and approaches in the current era of globalisation have accelerated business development and continued transformation. The coffee industry is a promising sector with significant economic potential, particularly in West Aceh Regency. This study aims to analyse the influence of an infinite mindset on the sustainability of coffee shop businesses, both directly and indirectly through innovation and learning ability as mediating variables. This study used an associative quantitative approach with a sample of 119 coffee shop owners or managers selected using purposive and convenience sampling techniques. Data were collected through questionnaires and analysed using the Partial Least Squares (PLS) method with the help of the SMART PLS 4 software. The results showed that an infinite mindset has a positive and significant effect on innovation and learning ability. Furthermore, both innovation and learning ability also have a positive and significant effect on business sustainability. An infinite mindset was also proven to have a significant indirect effect on business sustainability through these two mediating variables. These findings emphasise the importance of a long-term mindset and continuous learning in facing dynamic business competition.